Contribution Of Income And The Role Of Women In Household Decision-Making (A Study Of Women Vegetable Stall Traders In The Panorama Market, Bengkulu City) - Dessy Pratiwi Sukma; Muhammad Mustopa Romdhon; Gita Mulyasari (UNIVED Press, Dehasen University Bengkulu, 2025)
The role of women in household decision-making is essential to understanding the dynamics of gender relations, particularly in determining the relative dominance between men and women in household activities and overall family welfare. Purpose: This study aims to analyze the income contribution and decision-making role of female vegetable traders in household affairs at Panorama Market, Bengkulu City. Methodology: Data were collected through direct interviews with 40 respondents, using purposive sampling techniques, and supplemented with secondary data from relevant literature. The data were analyzed using descriptive statistical methods. Results: The average monthly income contribution of female vegetable traders is Rp2,248,110 or 54% of total household income, indicating a moderate contribution level. As much as 41.6% of household decisions were made independently by the wife, particularly in productive, domestic, and social aspects. Findings: Women play an important role in household decision-making and family welfare, both financially and in various aspects of decision-making. Novelty: This study highlights the dual role of informal female traders in traditional Indonesian markets, serving as both income earners and household decision-makers. Originality: By examining the relationship between economic contribution and gender-based decision-making dynamics in a rarely studied local context, this research enriches the literature on gender and the informal economy in Southeast Asia. Conclusion: A high economic contribution encourages women’s dominance in household decision-making. Strengthening business capital and promoting a more balanced division of domestic roles are expected to enhance overall household welfare. Type of Paper: Research Article.